2021
DOI: 10.1136/bmjnph-2021-000270
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional parameters and outcomes in patients admitted to intensive care with COVID-19: a retrospective single-centre service evaluation

Abstract: BackgroundCOVID-19 is an inflammatory syndrome caused by novel coronavirus SARS-CoV-2. Symptoms range from mild infection to severe acute respiratory distress syndrome (ARDS) requiring ventilation and intensive care. At the time of data collection, UK cases were around 300 000 with a fatality rate of 13% necessitating over 10 000 critical care admissions; now there have been over 4 million cases. Nutrition is important to immune function and influences metabolic risk factors such as obesity and glycaemic contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
2
4
0
3
Order By: Relevance
“…Moreover, nearly two-thirds exhibited low handgrip strength, while 27.1% of the patients were at higher risk of falling, according to the TUG test. The high degree of physical dysfunction was consistent with the results of other similar studies [ 20 , 21 , 22 ]. Several factors may explain the results, including sarcopenic obesity, inflammatory mediators, and insulin resistance [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, nearly two-thirds exhibited low handgrip strength, while 27.1% of the patients were at higher risk of falling, according to the TUG test. The high degree of physical dysfunction was consistent with the results of other similar studies [ 20 , 21 , 22 ]. Several factors may explain the results, including sarcopenic obesity, inflammatory mediators, and insulin resistance [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…The study data show that the COVID-19 patients admitted to intensive care in this study had a mean age of 58.8 years and were mostly male, which is consistent with other studies [ 20 , 21 , 22 ]. Overweight and obesity were highly prevalent in our cohort, as reported by other authors as well [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One study only looked retrospectively at the mean serum selenium level of 33 COVID-19 patients (out of 72 with mean age 57.1 ± 9.8 years) at Intensive Care Unit (ICU) admission (West London, UK, March–May 2020), finding it to be within the normal range despite a 33% mortality [ 32 ]. Voelkle and coworkers concluded that, even though selenium deficiency was found in 51% of 57 COVID-19 cases consecutively admitted between 17 March 2020 and 30 April 2020 at the Cantonal Hospital Aarau (Switzerland), “no association between low selenium levels and adverse clinical outcomes was found” [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Публикация T. Eden и соавт. свидетельствует, что гипергомоцистеинемия (определенная в статье как уровень более 15,5 мкмоль/л) в значительном числе случаев имела положительную корреляцию со степенью поражения легких, оцененной по компьютерной томограмме у 273 пациентов с COVID-19, что говорит о его значимости при тяжелом течении COVID-19 [32].…”
Section: дефицит B12 и метаболизм гомоцистеинаunclassified